Articulating Principals, Agents and Institutions in the EU - Mark McGovern; Nurcan Temel (European Regional Science Association (ERSA), 2005)
Principal agent problems arise frequently in situations of interdependence. Europe, with its various arrangements, is replete with principal agent problems that are mediated by institutions at various levels. While issues of water and land can provide a convenient focus, the essential problem is a deeper one. Decision making in principal agent situations has traditionally been considered in only a limited way. Current agency approaches seek to orient the interests of agents to those of the principal. More generalised formulations experience difficulties in reconciling interests. This is apparent not only in two-party forms but even more so in three-part(y) ones. In n-party environments things may appear to become simpler as n increases, but the problem may remain. An innovative exploration of a principal-agent situation which uses object-based concepts and simulations is presented in this paper. Different patterns of agent commitment are seen when it is applied to a European context. Suitable reconceptualisation of agency theory appears to have wide implications and applications. Its further development will allow more adequate specification of agency situations with immediate implications for policy and practice not only in Europe but in nations and regions around the world.
Keywords: 330